2019
DOI: 10.1002/cplu.201900024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slip‐Stack Self‐Assembly on Aggregation‐Induced Emission and Solid‐State Luminescence in 1,3‐Diarylpropynones

Abstract: Co-facial stacking can result in aggregation-caused quenching (ACQ) in conjugated organic luminogens. This study provides an attractive 'slip-stack' self-assembly approach which can eliminate the occurrence of ACQ. The obtained results from steady-state and time-resolved optical studies, along with X-ray diffraction and computational studies demonstrate aggregation-induced emission enhancement (AIEE) of a donor-π-acceptor based 1,3-diarylpropynone, namely 1-(naphthalenyl)-3-(pyren-1-yl)prop-2-yn-1-one (PYNAP).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
(86 reference statements)
2
19
0
Order By: Relevance
“…This additional factor justifies PLQYs increased by a factor 10 with respect to strictly similar emissive metallopolymers, without charged chain [35]. Samples with percentage quite higher 10% undergo aggregation caused quenching effect (ACQ) [53,54,55] related to rapid nonradiative decays of the excimers of neighboring fluorophores. Samples with percentages quite lower than 10% show poor emission, due to the scarce number of ligand moieties (where HOMO is located).…”
Section: Resultsmentioning
confidence: 99%
“…This additional factor justifies PLQYs increased by a factor 10 with respect to strictly similar emissive metallopolymers, without charged chain [35]. Samples with percentage quite higher 10% undergo aggregation caused quenching effect (ACQ) [53,54,55] related to rapid nonradiative decays of the excimers of neighboring fluorophores. Samples with percentages quite lower than 10% show poor emission, due to the scarce number of ligand moieties (where HOMO is located).…”
Section: Resultsmentioning
confidence: 99%
“…Wide angle XRD pattern of S1 powder and xerogel showed a reflection peaks at 2θ = 23.12°( d = 3.84 Å) and 2θ = 23.26°(d = 3.82 Å), which correspond to typical d-spacing values of π−π interaction. 61 The detailed calculations for π-interaction from PXRD was given in the Supporting Information. As evidenced from the PXRD pattern, d-spacing value for xerogel was slightly decreased than powder S1, indicating that π−π interaction in xerogel was higher than that of powder form.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To study the molecular packing of S1 in powder and xerogel, PXRD analysis was performed (Figure S11c). Wide angle XRD pattern of S1 powder and xerogel showed a reflection peaks at 2θ = 23.12° ( d = 3.84 Å) and 2θ = 23.26° ( d = 3.82 Å), which correspond to typical d -spacing values of π–π interaction . The detailed calculations for π-interaction from PXRD was given in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray analysis indicated that the naphthalene motif stabilizes the crystal array through elongated π−π interactions (3.466 Å) (Scheme 3). 100 5.2. Self-Isolation by Alkyl Chain and Bulky Groups.…”
Section: Structural Characteristics Found Inmentioning
confidence: 99%